Early Diagnosis of Sepsis in Purulent-Inflammatory Diseases of Soft Tissues - S.S. Atakov; T.Sh Atajonov (Zien Journals, 2023)
The following work is adapted and devoted to the development of methods for the first diagnosis of infection with purulent-inflammatory diseases of soft tissues, developed against the background of diabetes, using new and traditional methods for the diagnosis of sepsis. At the same time, it was noted that early diagnosis and timely surgical treatment made it possible to reduce generalization, development of purulent-inflammatory process and mortality.
Keywords: diabetes mellitus; surgical infection; sepsis